Relationships between spirituality and religiosity in dentistry academics in the state of Bahia - Ianderlei Andrade SOUZA; Marilei de Melo Tavares e SOUZA; Edgard Michel CROSATO; Sérgio Donha YARID (RGO: Revista Gaúcha de Odontologia, 2023)
ABSTRACT Objective: This study aims to evaluate the correlation between religiosity and spirituality in dental students in the state of Bahia. Methods: Cross-sectional study carried out with 266 dental students from the state of Bahia. To measure religious involvement, the Duke Religious Index (DUREL) was used, while the Spirituality Self Rating Scale (SSRS) was used for spirituality. Results: A total of 266 students were evaluated, with a mean age of 32 years (±11.9), most of them female (62.4%), of self-reported race/color (52.3%), with an income greater than three minimum wages (57.1%) and studying/working from the sixth to the tenth semester (41.0%). The correlations evidenced can be classified as weak for organizational religiosity (OR) (r = 0.406), moderate for non-organizational religiosity (RNO) (r = 0.589) and strong for intrinsic religiosity (RI) (r = 0.677). In the multivariate model, the ORN and RI dimensions proved to be predictors of spirituality, and the elevation of the former implies a consequent increase in spirituality. Conclusion: It is concluded that the RNO and RI dimensions are positively correlated with religiosity.